Chlamydia trachomatis RNA polymerase alpha subunit: sequence and structural analysis. - Gu, L (1995)
We describe the cloning and sequence analysis of the region surrounding the gene for the alpha subunit of RNA polymerase from Chlamydia trachomatis. This region contains genes for proteins in the order SecY, S13, S11, alpha, and L17, which are equivalent to Escherichia coli and Bacillus subtilis r proteins. The incorporation of chlamydial alpha subunit protein into the E. coli RNA polymerase holoenzyme rather than its truncated variant lacking the amino terminus suggests the existence of structural conservation among alpha subunits from distantly related genera.